Diabetic rats with high levels of endogenous dopamine do not show retinal vascular pathology - Allen, Rachael S.; Khayat, Cara T.; Feola, Andrew J.; Win, Alice S.; Grubman, Allison R.; Chesler, Kyle C.; He, Li; Dixon, Jendayi A.; Kern, Timothy S.; Iuvone, P. Michael; Thule, Peter M.; Pardue, Machelle T. (Frontiers in Neuroscience, 2023)
Purpose: Limited research exists on the time course of long-term retinal and cerebral deficits in diabetic rodents. Here, we investigated the temporal appearance of functional deficits (retinal, cognitive, and motor), retinal vascular pathology, and retinal dopamine levels in the Goto-Kakizaki (GK) rat model of Type II diabetes. Methods: In GK rats and Wistar controls, retinal neuronal function (electroretinogram), cognitive function (Y-maze), and motor function (rotarod) were measured at 1, 2, 4, 6, and 8 months of age. In addition, we evaluated retinal vascular function (functional hyperemia) and glucose and insulin tolerance. Retinas from rats euthanized at ≥ 8 months were assessed for vascular pathology. Dopamine and DOPAC levels were measured via HPLC in retinas from rats euthanized at 1, 2, 8, and 12 months. Results: GK rats exhibited significant glucose intolerance beginning at 4 weeks and worsening over time (p<0.001). GK rats also showed significant delays in flicker and oscillatory potential implicit times (p<0.05 to p<0.001) beginning at 1 month. Cognitive deficits were observed beginning at 6 months (p<0.05), but no motor deficits. GK rats showed no deficits in functional hyperemia and no increase in acellular retinal capillaries. Dopamine levels were twice as high in GK vs. Wistar retinas at 1, 2, 8, and 12 months (p<0.001). Conclusions: Retinal deficits were detectable prior to cognitive or motor deficits in GK rats. While retinal neuronal function was compromised, retinal vascular pathology was not observed, even at 12+ months. High endogenous levels of dopamine in the GK rat may be acting as an anti-angiogenic and providing protection against vascular pathology.